1997
DOI: 10.1017/s0033291796004187
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the onset of depression following a shared life event: a study of couples

Abstract: These results support the hypothesis that gender differences in rates of depression in the general population are, to a considerable extent, a consequence of role differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(88 citation statements)
references
References 46 publications
7
79
0
2
Order By: Relevance
“…A detailed and critical study of rolebased behaviour promises a major step forward in understanding sex differences in the frequency of affective disorder. Important developments in this area have been reported by Power and his colleagues (Lam & Power, 1991 ;Champion & Power, 1995) and by Nazroo et al (1997). I have set out elsewhere the aspects of roles that are likely to be significant (Bebbington, 1996).…”
Section: Role Involvementmentioning
confidence: 99%
“…A detailed and critical study of rolebased behaviour promises a major step forward in understanding sex differences in the frequency of affective disorder. Important developments in this area have been reported by Power and his colleagues (Lam & Power, 1991 ;Champion & Power, 1995) and by Nazroo et al (1997). I have set out elsewhere the aspects of roles that are likely to be significant (Bebbington, 1996).…”
Section: Role Involvementmentioning
confidence: 99%
“…22 In a community sample of couples, Nazroo and researchers found that women were more likely to experience depression after a stressful life event related to children, housing, or reproduction compared to their male partners. 23 As the effect did not hold for other life stressors, the researchers suggested that the association was because of women's increased roles in these areas.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one British study found that "significant involvement in domestic roles" by men in a household apparently acted as a protective factor against depression when a shared crisis involving "children, housing and reproduction" confronted both members of a couple. When the household was characterized by a pronounced gender-based division of labour, on the other hand, women were five times as likely as men to experience a depressive episode (Nazroo, Edwards and Brown, 1997). Adversities that are related to economic situation constitute another broad category of such situational factors.…”
Section: The Biological Plausibility Of Preventionmentioning
confidence: 99%